ENSURING THE HONOR AND DIGNITY OF CITIZENS IN THE NEW CONSTITUTION OF THE REPUBLIC OF UZBEKISTAN - Radjabov Ulugbek (Academia Science Repository, 2023)
The article is devoted to the concept of honor as a fundamental category of law. The article points out that the honor is the basis of abiding the law. And the main purpose of the state is to protect the honor and dignity of citizens. This purpose is achievable only if citizens also strive for their honour protection.